2010
DOI: 10.1160/th09-11-0792
|View full text |Cite
|
Sign up to set email alerts
|

FIX-Triple, a gain-of-function factor IX variant, improves haemostasis in mouse models without increased risk of thrombosis

Abstract: Engineered recombinant factor IX (FIX) with augmented clotting activity may prove useful for replacement therapy, but it has not been studied for risk of thrombosis. We used three mouse models to evaluate thrombosis risk associated with the FIX variant FIX-Triple, which has a 13-fold higher specific activity than wild-type FIX (FIX-WT). Protein infusion of FIX-Triple into haemophilia B mice was not thrombogenic, even at a dose of 13-fold higher than FIX-WT. Gene knock-in to generate mice that constitutively pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…More specific to F.IX, though, is the discovery of mutants with increased clotting activity. Alanine substitution mutation resulted in the artificial generation of F.IX-triple, which has ~10-fold greater specific activity than wild-type F.IX (211, 212). Additionally, a naturally occurring F.IX mutation (R338L), termed F.IX Padua, was discovered that has 5-10-fold higher activity (42, 213-215).…”
Section: Gene Therapies For Hemophlia Bmentioning
confidence: 99%
“…More specific to F.IX, though, is the discovery of mutants with increased clotting activity. Alanine substitution mutation resulted in the artificial generation of F.IX-triple, which has ~10-fold greater specific activity than wild-type F.IX (211, 212). Additionally, a naturally occurring F.IX mutation (R338L), termed F.IX Padua, was discovered that has 5-10-fold higher activity (42, 213-215).…”
Section: Gene Therapies For Hemophlia Bmentioning
confidence: 99%
“…144 This latter knockout model has in fact been used to generate a number of additional strains each of which expresses a single copy F9 gene from the “socket” located in the endogenous single copy mouse F9 gene locus. These strains include: mouse FIX expressing a mutation that alters the FIX Gla domain interaction with endothelium (K5AFIX) 145 defective human FIX having a missense mutation at a critical arginine in the catalytic domain (R333QFIX) 146; 147 defective human FIX having a nonsense mutation in the Gla domain that results in an early stop mutation (R29XFIX) 148 human FIX wild type (FIX-WT mouse) 147 human FIX carrying three mutations each of which increases the specific activity of the protein (“FIX Triple”). 147 …”
Section: The Hemophilia B Mouse Modelmentioning
confidence: 99%
“…defective human FIX having a missense mutation at a critical arginine in the catalytic domain (R333QFIX) 146; 147 …”
Section: The Hemophilia B Mouse Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In an early study, we demonstrated that replacement of arginine 338 by alanine (R338A) was associated with an ϳ 3-fold increase in the protein specific activity in murine models of HB receiving AAV-FIX-R338A 9 as later confirmed in other models. 10,11 Recently, we described a naturally occurring gain-of-function mutation in humans characterized by leucine at position 338 (R338L), which exhibits normal antigen levels, but an ϳ 8-fold higher specific activity. 12 Notably, the arginine at position 338 in FIX is conserved among mammals, and this region of the enzyme appears to be part of the substrate exosite for factor X.…”
Section: Introductionmentioning
confidence: 99%